Supply chains, maintenance and safety in the Australian airline industry. (September 2015) - Gregson, Sarah; Hampson, Ian; Junor, Anne; Fraser, Doug; Quinlan, Michael; Williamson, Ann
This article examines potential regulatory and safety problems arising from the outsourcing and offshoring of heavy aircraft maintenance. We raise questions about the advisability of using increasingly complex supply chains in the aircraft maintenance industry where safety standards are paramount. Greater disarticulation of maintenance work makes regulatory oversight more convoluted and expensive to do thoroughly and transparently. Using a Pressure, Disorganisation and Regulatory Failure model, the article highlights how new work arrangements involving increased use of supply chains are developing more quickly than adequate airline, union and regulator responses to the safety problems engendered by those changes. In often heated industrial debates between licensed aircraft maintenance engineers (LAMEs) and airline managers about business needs and safety, we urge that more attention be paid to LAME concerns about outsourcing.